Lege woorden, volle bekers, tevreden gesprekspartners – enkele notities over conversatieroutinen in een gespreksboekje uit de 16de eeuw - Grzega, Joachim (Acta Neerlandica, 2024)
Empty words, full goblets, contented interlocutors – some notes on conversational routines in a colloquy from the 16th century     The article analyzes the three conversations in the 1527 version of Noel van Barlainmont’s Dutch–French Vocabulare with regard to aspects of Dutch (or Flemish) historical pragmatics. The analysis shows: (1) some parallel language structures in both languages that can be seen as likely authentic: (a) a single address pronoun; (b) address terms (kinship terms, especially the today semantically more restrictive “nephew/niece”, and “friend” for a customer), (b) (full and elliptical) greetings with the pattern “God give you [+ tomorrow/day/evening]”, (c) the high frequency of imperatives for directive speech-acts (and the infrequent use of positive, negative, and indirect politeness), (d) the high frequency of imperative for commissive (and commissive-directive) language acts, (e) farewell phrases with the element “God”; (2) noteworthy content structures: (a) “adequate rudeness” in bargaining, (b) lying by a debtor in front of a creditor and a potential bail, (c) the small-talk topic “war and peace” and (d) prolonged leave-taking scenes; (3) Flemish peculiarities (in contrast to French): (a) the more frequent use of “my” before address terms, (b) the pattern “Hoe vaar jij?” after the greeting formula, (c) the connection of “Yes” and “No” with pronouns, (d) Ic danck v, ic bedanck v, grooten danck and, possibly, God segen u as variants of thanking, (e) in addition to te gode, there is also the French borrowing adieu.